Prognostic awareness and prognostic information preferences among advanced cancer patients in Kenya - Hussein Elias; Semra Ozdemir; Joann Bairavi; Emmah Achieng; Eric A. Finkelstein (AOSIS, 2024)
Background: Cancer is the third leading cause of death in Kenya. Yet, little is known about prognostic awareness and preferences for prognostic information. Aim: To assess the prevalence of prognostic awareness and preference for prognostic information among advanced cancer patients in Kenya. Setting: Outpatient medical oncology and palliative care clinics and inpatient medical and surgical wards of Moi Teaching and Referral Hospital (MTRH) in Eldoret, Kenya. Methods: The authors surveyed 207 adults with advanced solid cancers. The survey comprised validated measures developed for a multi-site study of end-of-life care in advanced cancer patients. Outcome variables included prognostic awareness and preference for prognostic information. Results: More than one-third of participants (36%) were unaware of their prognosis and most (67%) preferred not to receive prognostic information. Increased age (OR = 1.04, 95% CI: 1.02, 1.07) and education level (OR: 1.18, CI: 1.08, 1.30) were associated with a higher likelihood of preference to receive prognostic information, while increased symptom burden (OR= 0.94, CI: 0.90, 0.99) and higher perceived household income levels (lower-middle vs low: OR= 0.19; CI: 0.09, 0.44; and upper middle- or high vs low: OR= 0.22, CI: 0.09, 0.56) were associated with lower odds of preferring prognostic information. Conclusion: Results reveal low levels of prognostic awareness and little interest in receiving prognostic information among advanced cancer patients in Kenya. Contribution: Given the important role of prognostic awareness in providing patient-centred care, efforts to educate patients in Kenya on the value of this information should be a priority, especially among younger patients.